Tindakan Keperawatan pada Klien, Keluarga dan Kader Kesehatan Jiwa terhadap Klien Isolasi Sosial di Komunitas - Rachmawati, Umi; Keliat, Budi Anna; Wardani, Ice Yulia (Jurnal Keperawatan Jiwa, 2014)
Social isolation is one of nursing diagnosis that found on the client's nursing schizophrenia. The aims of this paper were known outcomes of nursing care such as Socialization Therapeutic Group Activities (TAKS), Social Skill Training (SST) and Family psychoeducation (FPE) and roles of mental health workers care for social isolation clients by Community as Partner Model approach. Socialization Therapeutic Group Activities (TAKS), Social Skill Training (SST), family social support by the Family psychoeducation (FPE), as well as the activities of mental health workers to visite the 4th of social isolation clients with schizophrenia. The results showed a decrease in signs and symptoms of clients with increased social skills. Was recommend research on nursing care with empowering mental health workers care for social isolation clients with more respondents.